(untitled) (Ingenio Magno, 2016)
This article presents the design process and implementation of a microprocessor for educational purposes based on basic digital components, with the goal of making it easier to understand the architecture and functioning of microprocessors. The process is carried out in three main sections, transfer instructions between registers, control flow (unconditional jumps), and logical and arithmetic operations. In order to perform the system check, analog to digital conversion ADC and digital to analog conversion DAC peripherals were added, with the goal of implementing an application of temperature measurement with an LM35 sensor, to obtain its magnitude in an industrial protocol of communication of 4mA to 20mA. The implementation of said microprocessor is carried out with the software ISE Design Suite 14.2 from XILINX, and is implemented on the Spartan-3 FPGA development board.